Multimedia Pembelajaran Konsep Bilangan Pecahan Berdasarkan Contoh Pengalaman Anak Sehari-Hari Pada Sekolah Dasar - sri siswanti (Jurnal Ilmiah SINUS, 2012)
Learning of mathematics in the classroom emphasized the links between mathematical concepts with everyday experience of children. In addition, the need to apply the mathematical concepts that have been re-possessed child in everyday life or in other areas is very important. Linking real life experiences of children with mathematical ideas in the classroom is important so that meaningful learning (ollive John, 2002 Munirah Ghazali, 2005)This study aimed to determine the effect of the use of multimedia on learning outcomes based on the relationship between fractions of fractions with examples of children's daily experiences.The results showed that the learning system can be made easier for students to understand the concept of fractions. Results using instructional media can be seen from the average value of each group, for the treatment group was 80.20 and the average value for the control group was 61.20. Based on the questionnaires to the respondents in the treatment group, 79% stated that the operation, contents, delivery of content (tutorials) in the form of images and text and easy to use learning strategies.Key words: Fractions, multimedia, learning